Pancreatic cancer: A review of clinical diagnosis, epidemiology, treatment and outcomes - McGuigan, Andrew; Kelly, Paul; Turkington, Richard C; Jones, Claire; Coleman, Helen G; McCain, R Stephen (World journal of gastroenterology : WJG, 2018)
This review aims to outline the most up-to-date knowledge of pancreatic adenocarcinoma risk, diagnostics, treatment and outcomes, while identifying gaps that aim to stimulate further research in this understudied malignancy. Pancreatic adenocarcinoma is a lethal condition with a rising incidence, predicted to become the second leading cause of cancer death in some regions. It often presents at an advanced stage, which contributes to poor five-year survival rates of 2%-9%, ranking firmly last amongst all cancer sites in terms of prognostic outcomes for patients. Better understanding of the risk factors and symptoms associated with this disease is essential to inform both health professionals and the general population of potential preventive and/or early detection measures. The identification of high-risk patients who could benefit from screening to detect pre-malignant conditions such as pancreatic intraepithelial neoplasia, intraductal papillary mucinous neoplasms and mucinous cystic neoplasms is urgently required, however an acceptable screening test has yet to be identified. The management of pancreatic adenocarcinoma is evolving, with the introduction of new surgical techniques and medical therapies such as laparoscopic techniques and neo-adjuvant chemoradiotherapy, however this has only led to modest improvements in outcomes. The identification of novel biomarkers is desirable to move towards a precision medicine era, where pancreatic cancer therapy can be tailored to the individual patient, while unnecessary treatments that have negative consequences on quality of life could be prevented for others. Research efforts must also focus on the development of new agents and delivery systems. Overall, considerable progress is required to reduce the burden associated with pancreatic cancer. Recent, renewed efforts to fund large consortia and research into pancreatic adenocarcinoma are welcomed, but further streams will be necessary to facilitate the momentum needed to bring breakthroughs seen for other cancer sites.